2017
DOI: 10.1590/0103-8478cr20160024
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and average genetic components in green corn genotypes

Abstract: This study aimed to evaluate the inbreeding depression and average genetic components in seven hybrids and two open pollinated cultivars for green corn production, as well as to select the best genotypes in order to obtain base populations for inbred lines extraction. The experiment was carried out in a randomized complete block design with four replications, in a split plot design, with inbreeding levels arranged in the plots and the different genotypes distributed over the subplots, in the municipality of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
(17 reference statements)
3
7
0
1
Order By: Relevance
“…According to quadratic component magnitudes, the contribution of the GCA effect was higher for AN, SI, PH, EH, and GLS severity, which was an indication of additive effects that controlled these traits (Table 3). Similar results were also observed by Freitas Jr., Amaral Jr., Pereira, Cruz, and Scapim (2006) and Kuki et al (2017), who also observed higher importance for the additive effects for PH and EH, as well as flowering period. The contribution of the non-additive effects was higher only for WS severity and GY.…”
Section: Resultssupporting
confidence: 88%
“…According to quadratic component magnitudes, the contribution of the GCA effect was higher for AN, SI, PH, EH, and GLS severity, which was an indication of additive effects that controlled these traits (Table 3). Similar results were also observed by Freitas Jr., Amaral Jr., Pereira, Cruz, and Scapim (2006) and Kuki et al (2017), who also observed higher importance for the additive effects for PH and EH, as well as flowering period. The contribution of the non-additive effects was higher only for WS severity and GY.…”
Section: Resultssupporting
confidence: 88%
“…Table 1 indicates that, among the traits evaluated, those related to production (EW and GW) had the highest inbreeding depression (ID), with means reaching 50.43% (EW) and 50.32% (GW). Several studies reported ID higher for the production variable than PH and EH (Scapim et al, 2006;Garbuglio et al, 2009;Bernini et al, 2013;Kuki et al, 2017). Good and Hallauer (1977) observed that production is the most affected variable by inbreeding in any degree of homozygosity.…”
Section: Resultsmentioning
confidence: 99%
“…Good and Hallauer (1977) observed that production is the most affected variable by inbreeding in any degree of homozygosity. According to Kuki et al (2017) and Bernini et al (2013), inbreeding depression for PH and EH is lower than for EW and GW, because the dominance effects are less important in these traits.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology has been widely adopted by several authors earlier, aiming to obtain the best populations for line extraction, and consequently reducing self-fertilization and evaluation costs of lines (Kuki et al, 2017). However, due to the dynamic of hybrid releases in the market, many maize hybrids do not have information about either their inbreeding depression or m+a and d, even in the case when this information is very valuable to initiate new breeding populations and continue the breeding cycles.…”
Section: Introductionmentioning
confidence: 99%